LITHOSPHERIC STRUCTURE BENEATH TRANS-CARPATHIAN TRANSECT FROM PRECAMBRIAN PLATFORM TO PANNONIAN BASIN: CELEBRATION 2000 SEISMIC PROFILE CEL05 - Grad M.; Guterch A.; Janik T.; Keller G.R.; Hegedus E.; Vozár J.; Ślaczka A.; Tiira T.; Yliniemi J. (My University, 2006)
In 2000, a consortium of European and North American institutions completed a huge active source seismic experiment focused on central Europe, the Central European Lithospheric Experiment Based on Refraction or CELEBRATION 2000. This experiment primarily consisted of a network of seismic refraction profiles that extended from the East European craton, along and across the Trans-European suture zone region in Poland to the Bohemian massif, and through the Carpathians and eastern Alps to the Pannonian basin. The longest profile CEL05 (1420 kin) is the focus of this paper. The resulting two-dimensional tomographic and ray-tracing models show strong variations in crustal and lower lithospheric structure. Clear crustal thickening from the Pannonian basin (24-25 km thick) to the Trans-European suture zone region (~50 km), together with the configuration of the lower lithospheric reflectors, suggests northward subduction of mantle underlying Carpathian-Pannonian plate under the European plate. This, however, conflicts with strong geological evidence for southward subduction, and we present three tectonic models that are to not totally mutually exclusive, to explain the lithospheric structure of the area: (1) northward "old" subduction of the Pannonian lithosphere under the East European craton in the Jurassic-Lower Cretaceous, (2) a collisional zone containing a "crocodile" structure where Carpatho-Pannonian upper crust is obducting over the crystalline crust of the East European craton and the Carpathian-Pannonian mantle lithosphere is underthrusting cratonic lower crust, and (3) lithosphere thinning due to the effects of Neogene extension and heating with the slab associated with "young" subduction southward in the Miocene having been either detached and/or rolled back to the east. In the last case, the northwestward dipping in the lithosphere can be interpreted as being due to isotherms that could represent the lithosphere/asthenosphere boundary in the Pannonian region. Copyright 2006 by the American Geophysical Union.
Keywords: Cretaceous; Jurassic; Miocene; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен